A Case Study of Source Triangulation: Using Artifacts as Knowledge Elicitation Tools in Healthcare Space Design. (December 2015) - Papautsky, Elizabeth Lerner; Crandall, Beth; Grome, Anna; Greenberg, James M.
The importance of triangulating multiple sources of data in the design of tools, technology, and clinical workspaces has not been explicitly addressed in the applied human factors literature. In this paper, we describe an applied human factors case study in which Cognitive Task Analysis was used to triangulate the needs, goals, and design requirements from various stakeholder groups for the design of a Newborn Intensive Care Unit. To facilitate development of common ground on the design goals, in our interviews, we asked questions about (a) stated design goals to elicit the perspectives of meaning across the user groups and (b) schematic renderings of the proposed space. They served as a way to establish a representative definition of each design goal accounting for the perspectives of all user groups. We found that each role brought a perspective and a level of detail based on his/her role goals and lived experience to the design goals. The goals and tradeoffs illuminated by our approach can only be identified when multiple perspectives are collected. Source triangulation should be pursued as part of standard human factors methods to achieve design and evaluation objectives in the context of complex sociotechnical systems.